Transcriptomic analysis reveals the contribution of QMrl-7B to wheat root growth and development - Liu, Jiajia; Zhi, Liya; Zhang, Na; Zhang, Wei; Meng, Deyuan; Batool, Aamana; Ren, Xiaoli; Ji, Jun; Niu, Yanxiao; Li, Ruiqi; Li, Junming; Song, Liqiang (Frontiers in Plant Science, 2022)
Roots are the major organs for water and nutrient acquisition and substantially affect plant growth, development and reproduction. Improvements to root system architecture are highly important for the increased yield potential of bread wheat. QMrl-7B, a major stable quantitative trait locus (QTL) that controls maximum root length (MRL), essentially contributes to an improved root system in wheat. To further analyze the biological functions of QMrl-7B in root development, two sets of Triticum aestivum near-isogenic lines (NILs), one with superior QMrl-7B alleles from cultivar Kenong 9204 (KN9204) and another with inferior QMrl-7B alleles from cultivar Jing 411 (J411), were subjected to transcriptomic analysis. Among all the mapped genes analyzed, 4871 genes were identified as being differentially expressed between the pairwise NILs under different nitrogen (N) conditions, with 3543 genes expressed under normal-nitrogen (NN) condition and 2689 genes expressed under low-nitrogen (LN) condition. These genes encode proteins that mainly include NO3- transporters, phytohormone signaling components and transcription factors (TFs), indicating the presence of a complex regulatory network involved in root determination. In addition, among the 13524 LN-induced differentially expressed genes (DEGs) detected in this assay, 4308 were specifically expressed in the NILKN9204 which brings superior alleles, and 2463 were expressed specifically in the NILJ411 which brings inferior alleles. These DEGs reflect different responses of the two sets of NILs to varying N supplies, which likely involve LN-induced root growth. These results explain the better-developed root system and increased root vitality conferred by the superior alleles of QMrl-7B and provide a deeper understanding of the genetic underpinnings of root traits, pointing to a valuable locus suitable for future breeding efforts for sustainable agriculture.